2006
DOI: 10.1128/iai.00797-06
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis Minor Fimbriae Are Required for Cell-Cell Interactions

Abstract: Two distinctive types of fimbriae have been identified in Porphyromonas gingivalis. In this report, we demonstrate that minor fimbriae are involved in P. gingivalis autoaggregation and colonization. A mutant with a deficiency in minor fimbriae can bind to a saliva-coated surface but does not form microcolonies as the wild-type strain does.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
67
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 19 publications
(12 reference statements)
8
67
1
1
Order By: Relevance
“…Studies have demonstrated a role for long fimbriae in adherence to and invasion of gingival epithelial cells, bone resorption, co-aggregation with other oral isolates, and biofilm formation (Amano et al, 2004;Hamada et al, 1998;Lamont & Jenkinson, 1998). Interestingly, it was recently shown that the short fimbriae, unlike the long fimbriae, are required for autoaggregation (Lin et al, 2006), indicating that these two surface structures have distinctive functions. The in vivo signals that trigger the expression of genes involved in the biogenesis of fimbriae are not known; however, it has been shown that expression is affected by environmental and nutritional parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated a role for long fimbriae in adherence to and invasion of gingival epithelial cells, bone resorption, co-aggregation with other oral isolates, and biofilm formation (Amano et al, 2004;Hamada et al, 1998;Lamont & Jenkinson, 1998). Interestingly, it was recently shown that the short fimbriae, unlike the long fimbriae, are required for autoaggregation (Lin et al, 2006), indicating that these two surface structures have distinctive functions. The in vivo signals that trigger the expression of genes involved in the biogenesis of fimbriae are not known; however, it has been shown that expression is affected by environmental and nutritional parameters.…”
Section: Discussionmentioning
confidence: 99%
“…CLSM analysis of the biofilms formed by the ATCC 33277 fimR and fimS mutants showed that they produced biofilms that were distinct from the wild-type strain and also from each other, with rough and heterogeneous biofilms suggesting an apparent reduction of microcolony contacts. In vitro analysis of ATCC 33277 fimA and mfa1 mutants has shown FimA to be involved in adhesion of P. gingivalis to saliva-coated glass surfaces (26) and cultured KB epithelial cells (51), while mfa1 expression mediates cell aggregation (26). Neither the fimA nor mfa1 mutants formed a confluent biofilm (26).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of genes important for P. gingivalis fimbriation in the fimS and fimR mutants. It has been shown that production of the fimbrillins Mfa1 and FimA is essential for biofilm formation by P. gingivalis ATCC 33277 (26). Furthermore, it has been shown that FimR binds directly to the mfa1 promoter region (54) and to the promoter of the fimbriationassociated gene fimX that is upstream of fimA (37) (annotated as pg2130 in the W83 genome [36] and pgn_0178 in the recently released ATCC 33277 genome sequence [34]).…”
Section: Vol 192 2010 Fimr and Fims In P Gingivalis Biofilm 1337mentioning
confidence: 99%
See 1 more Smart Citation
“…Two distinctly different fimbriae are present on the P. ginigvalis cells; major or long, a 49 kDa protein, encoded by fimA gene and minor or short fimbriae composed of 67 kDa protein, encoded by mfa1 gene. [29]. It has been shown that fimbriae activate both humoral and cellular responses and inactivation of fimA gene reduces periodontal bone loss in gnotobiotic rats.…”
Section: Virulence Factors Of P Gingivalismentioning
confidence: 99%